2019
DOI: 10.5944/reop.vol.30.num.2.2019.25338
|View full text |Cite
|
Sign up to set email alerts
|

Los programas de educación emocional happy 8-12 and happy 12-16. Evaluación de su impacto en las emociones y el bienestar//The emotional education programs happy 8-12 and happy 12-16. Evaluation of their impact in emotions and well-being

Abstract: RESUMENDurante los últimos años se ha visto confirmada la importancia de las variables emocionales y de bienestar para un correcto desarrollo académico y personal del alumnado. Por este motivo ha existido un auge en las intervenciones y programas que trabajan estas variables. El objetivo de la presente investigación es conocer la diferencia existente entre las variables emocionales y de bienestar en alumnado de primaria y de secundaria después de haber participado en los programas de Educación Emocional Happy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 12 publications
0
5
0
14
Order By: Relevance
“…This finding is congruent with and corroborates outcomes reported by previous studies, such as those by Garrosa et al [32] and Andrés et al [31], which denoted the importance of working on emotional education in classrooms. This aspect had already been indicated by Pena et al [17] and has since been reiterated in numerous studies [33][34][35][36]. These cognitive re-evaluation processes do not only exert influence in the realm of emotions, they also facilitate the very regulation of cognitive processes and metacognition.…”
Section: Discussionmentioning
confidence: 69%
“…This finding is congruent with and corroborates outcomes reported by previous studies, such as those by Garrosa et al [32] and Andrés et al [31], which denoted the importance of working on emotional education in classrooms. This aspect had already been indicated by Pena et al [17] and has since been reiterated in numerous studies [33][34][35][36]. These cognitive re-evaluation processes do not only exert influence in the realm of emotions, they also facilitate the very regulation of cognitive processes and metacognition.…”
Section: Discussionmentioning
confidence: 69%
“…Different analyses were carried out, including correlations among variables, regression, and implementation of the General Linear Model (GLM) for repeated measures. The results obtained and published in different articles (Filella et al, 2016;Cabello, 2018;Cabello Cuenca et al, 2019;Ros-Morente et al, 2019;Filella Guiu, 2022, among others) after a pre-post design with a control group showed that training with the Happy 8-12 software for an academic year significantly improves emotional skills and reduces students' levels of anxiety (p < 0.001 in both cases), improving at the same time other variables. Although the effect of this learning was discreet, it should be recalled that these variables-emotional skills and the social climate of the classroom-require an extended time and training to change completely and will not show definitive progress until more training is implemented.…”
Section: Results Of Application Of the Program In Primary Schoolmentioning
confidence: 91%
“…The first program tested on a population of students was the primary education program, i.e., Happy 8-12, which was used at several primary schools in the city of Lleida (Spain) with a total sample of 576 students (Cabello, 2018;Cabello Cuenca et al, 2019).…”
Section: Results Of Application Of the Program In Primary Schoolmentioning
confidence: 99%
“…Se optó por textos editados bajo las directrices de la LOMCE, que fomenta el protagonismo de las competencias, aunque Montero-Pau et al (2018) indican que el tratamiento de la Educación para la Salud no ha mejorado con el cambio normativo. Esta circunstancia podría estar asociada a la carencia observada en este trabajo de contenidos relacionados con la salud mental y emocional, pese a su importancia en el bienestar y desarrollo del niño en esta etapa educativa (Cabello et al, 2019).…”
Section: Discusión Y Conclusionesunclassified